THE EFFECTIVENESS OF USING THINK-WRITE-PAIR-SHARE TECHNIQUE IN TEACHING WRITING - Mutia Mutia (PROJECT (Professional Journal of English Education), 2021)
The aim of this research is to figure out the use of the think-write-pair-share (TWPS) technique in writing. The method was the quantitative method. The population were tenth-grade students at one of vocational school in Cipanas in the academic year 2020/2021. The sample was 72 students that were divided into control class and experimental class. The experimental class was the class which learn writing recount text through think-write-pair-share (TWPS) technique, while control class was the one which used conventional method. The collected data were analyzed by using T-Test. The result showed that the value of T-test (0.027) was lower (<) than 0,05. Thus, the alternative hypothesis (Ha) was accepted. This meant that there was the difference between the class taught by think-write-pair-share (TWPS) technique and conventional method. Here, the students learned by using think-write-pair-share (TWPS) tended to be able to share their opinion in recount text. They also became more active. This implies that the think-write-pair-share (TWPS) technique can be used in teaching writing.Keywords:  Think-Write-Pair-Share Technique, Writing, Recount Text.